Optimisation of supplemental light systems in Norwegian tomato greenhouses - A simulation study. (March 2022) - Wacker, Jan-David; Verheul, Michél J.; Righini, Isabella; Maessen, Henk; Stanghellini, Cecilia
Abstract : Tomato greenhouses at high latitudes (≥58°North) require supplemental light to enable high yields and year-round production. Supplemental light systems can differ in lamp type, high-pressure sodium (HPS) or light emitting diode (LED), and also vary in lamp capacity. Based on a combined greenhouse climate, tomato yield, and greenhouse economics model, a methodology was developed, for determining the optimal supplemental light system, dependent on local climate and economic conditions. Two optimisation objectives were considered separately, maximal energy use efficiency (EUE) and maximal net financial result (NFR). The developed methodology was applied to four different greenhouse locations in Norway. At each location, both optimisation objectives were reached with LEDs. The optimal lamp capacities range from 256 to 341 μmol m −2  s −1 (maximal EUE) and 302–323 μmol m −2  s −1 (maximal NFR). The economically optimal lamp capacity is little sensitive to climate conditions. At the lamp type respective NFR maxima, LEDs resulted, on average, in 10% higher tomato yield, 102.2 NOK m −2 year −1 higher NFR, and 35% higher EUE. Consequently, switching from HPS lamps to LEDs enables increasing productivity, energy efficiency and profitability of greenhouse tomato production. Furthermore, the difference between EUE and NFR optima was, on average, 24% lower in terms of EUE and 56% lower in terms of NFR, when using LEDs instead of HPS lamps. On farm-scale, the proposed methodology can be used as decision-support-tool for selecting an efficient and profitable supplemental light system for greenhouse tomato production, dependent on local climate and economic conditions. Graphical abstract: Image 1 Highlights: A model-based methodology for optimising greenhouse lamp type and capacity is presented. The methodology was applied to four greenhouse locations in Norway. LEDs with capacities between 256 and 341 μmol m −2  s −1 reached maximal energy use efficiency. LEDs with capacities between 302 and 323 μmol m −2  s −1 reached maximal net financial results. Economically optimal lamp capacity is little sensitive to climate conditions.